Blunt thoracic trauma in children - Balci, AE; Kazez, A; Eren, S; Ayan, E; Özalp, K; Eren, MN (Elsevier Science Bv, 2004)
Objective: Thoracic injuries are uncommon in children and few report present on blunt ones. Methods: Between 1994 and 2003, 137 children with blunt thoracic injury were reviewed. Results: The mean age of children was 6.9 +/- 7.3 (1-16) years. Etiology was falls in 46.7%, traffical accidents in 51% and abuse in 2.2%. Average height in fallen-down cases was 6.4 +/- 2 (range: 3-11) m. Calculated mean kinetic energy transfer to body was 1923 +/- 1056 J. When first seen, 70% (82/117) of the patients had vital signs that were within normal limits. Forty-two (35.9%) children had isolated thoracic injury. Associated injuries were present in 75 (64.1%) children. Head injury was the most common associated injury present in 33 (28.2%). Pulmonary contusion was the most common thoracic injury with 68 (49.6%). Seventeen (12.4%) required surgery, 11 (8%) of them were thoracic (4 for diaphragmatic tear, 2 for flail chest, 2 for tracheobronchial injuries, 2 for laceration, 1 for esophageal rupture). Surgical group had higher ISS (26.8 vs 36.2, P = 0.001). Fifteen were lost (10.9%): There were lethal injuries in 7; chest tube treatment in 3; intensive care unit management in 2; mechanical support in 2 and observation in 1 patient. No death occurred for operations. Mortality rate was the lowest at injuries to chest alone and the highest for multi-system injuries (P < 0.05). The hospital length of stay for averaged 13.4 +/- 8.8 (range: 4-49) days. Conclusion: Associated injury is the most important mortality factor. Thoracic operations can be performed with minimal morbidity and without mortality in children with blunt thoracic trauma. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: blunt thoracic truma; children; fall